Enhanced Triethylamine-Sensing Characteristics of SnS2/LaFeO3 Composite - Hong Wu; Xiaobing Wang; Yuxiang Chen; Xiaofeng Wang (Chemosensors)
Triethylamine (TEA), a volatile organic compound (VOC), has important applications in industrial production. However, TEA has an irritating odor and potential toxicity, making it necessary to develop sensitive TEA gas sensors with high efficiency. This study focused on preparing LaFeO3 nanoparticles modified by SnS2 nanosheets (SnS2/LaFeO3 composite) using a hydrothermal method together with sol–gel technique. According to the comparison results of the gas-sensing performance between pure LaFeO3 and SnS2/LaFeO3 composite with varying composition ratios, 5% SnS2/LaFeO3 sensor had a sensitivity for TEA that was 3.2 times higher than pure LaFeO3 sensor. The optimized sensor operates at 140 °C and demonstrates strong stability, selectivity, and long-term durability. Detailed analyses revealed that the SnS2 nanosheets enhanced oxygen vacancy (OV) content and carrier mobility through heterojunction formation with LaFeO3. This study provides insights into improving gas-sensing performance via p-n heterostructure design and proposes a novel LaFeO3-based material for TEA detection.